Evidence of an evolutionary‐developmental trade‐off between drag avoidance and tolerance strategies in wave‐swept intertidal kelps (Laminariales, Phaeophyceae). Issue 1 (11th January 2016) - Starko, Samuel; Martone, Patrick T.
Abstract : Kelps are a clade of morphologically diverse, ecologically important habitat‐forming species. Many kelps live in wave‐swept environments and are exposed to chronic flow‐induced stress. In order to grow and survive in these harsh environments, kelps can streamline (reducing drag coefficient) to avoid drag or to increase attachment and breakage force to tolerate it. We aimed to quantify the drag tolerance and streamlining strategies of kelps from wave‐swept intertidal habitats. We measured drag coefficient and tenacity of populations from eight kelp species over a wide range of sizes to determine whether kelps avoid dislodgement by reducing drag coefficient or by increasing tenacity as they grow, and whether these traits are traded off. We employed phylogenetic comparative methods to rule out potentially confounding effects of species' relatedness. There was a significant negative relationship between drag avoidance and tolerance strategies, even after incorporating phylogeny. Kelps that were more tenacious were less able to reduce drag, resulting in a continuum from "tolerators" to "streamliners, " with some species demonstrating intermediate, mixed strategies. Drag and tenacity were correlated with geometric properties (i.e., second moment of area) of the stipe in large kelps. Results presented in this study suggest that kelps are either strong or streamlined, but not both. This continuum is consistent with avoidance and tolerance trade‐offs that have been documented in many different biological systems and may have widespread implications for the evolution of large macroalgae, perhaps driving morphological diversity within this group.